Estudio de Prefactibilidad para la Exportación de Manteca de Cacao desde Ibagué (Colombia) hacia Países Bajo (2022)
The purpose of this pre-feasibility study is to establish the viability of exporting cocoa butter to the Netherlands from Ibagué (Colombia), since it seeks to take advantage of the benefits and uses that this product brings to the confectionery sector, which makes it desirable and demanded by the Dutch country. Therefore, to carry out this project, aspects of foreign trade have been taken into account, such as statistics and background within the market; additionally, demand and supply are developed and analyzed along with their prices, in addition to specifying a technical plan to fully comply with the necessary processes, and also a financial plan with which a successful management of the company can be carried out. Taking into account the above, it can be indicated that it has been possible to determine the feasibility of exporting to the Netherlands market.